Replacement and Immunomodulatory Activities of 20% Subcutaneous Immunoglobulin Treatment: A Single-Center Retrospective Study in Autoimmune Myositis and CVID Patients - Danieli, Maria Giovanna; Verga, Jacopo Umberto; Mezzanotte, Cristina; Terrenato, Irene; Svegliati, Silvia; Bilo, Maria Beatrice; Moroncini, Gianluca (Frontiers in Immunology, 2022)
Background: Immunoglobulin (Ig) replacement therapy represents a life-saving treatment in primary antibody deficiencies. The recent introduction of subcutaneous Ig (SCIg) administration brings a significant improvement in quality of life for patients, compared to the traditional intravenous administration. In recent years, an additional role has been proposed for Ig therapy for various anti-inflammatory and immune-mediated diseases. Consequently, the use of SCIg has expanded from immunodeficiencies to immune-mediated diseases, such as polymyositis (PM) and dermatomyositis (DM). Given the rarity of these conditions, it is still difficult to evaluate the real impact of SCIg treatment on PM and DM, and additional data are constantly required on this topic, particularly for long-term treatments in real-life settings. Aim: This study aimed to improve the knowledge about the anti-inflammatory and immunomodulatory effects of SCIg treatment for myositis and provide further evidence about its replacement activity. To this aim, a long-term evaluation of the effectiveness of 20% human SCIg treatment (Hizentra®, CSL Behring) was carried out in patients with PM/DM and common variable immunodeficiency (CVID) in care at our Center. Results: Results support the beneficial effect and tolerability of long-term 20% SCIg therapy in PM/DM patients, reporting a significant improvement in creatine kinase levels, muscle strength, dysphagia, disease activity (MITAX score), disability (HAQ-DI score) and skin conditions. Even CVID patients reported an improvement in all the considered effectiveness parameters at the end of 20% SCIg therapy. Conclusions: Taken together, we provide clear evidence that 20% SCIg treatment represents a viable treatment for PM/DM and CVID patients and a valid therapeutic alternative to IVIg, with important advantages for patients' quality of life.